Analysis of Smart Villages as Public Policy Implementation in Pakatto Village, Bontomarannu District, Gowa Regency - Tahir, Muh. Zulkifli; Kurnia, Indra; Kurra, Sudiarti Dewi (PINISI Discretion Review, 2025)
The aim of this research is to analyze the smart village program as in implementation of public policy, supporting and inhibiting factors for implementation as well as the impact of the smart village program on the community in Pakatto Village, Bontomarannu District, Gowa Regency. The type of research used is descriptive qualitative, because the main data sources in the research are the results of interviews and the actions of the people interviewed as well as observations about situations and conditions found in the field. The research informants were villages and Pakatto village community, Gowa Regency Community Empowerment Service Office Staff, Village Community Development and Empowerment Program Staff of the Ministry of Home Affairs Regional Management Consultant of South Sulawesi and Gowa Regency Digital Ambassadors. Based on research that has been carried out, Pakatto Village, since being designated by the Ministry of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia as the location for the third phase of the smart village program in 2023, has implemented six pillars of smart villages, namely smart governance, smart community, smart economy, smart environment, smart mobility and smart living. A fairly prominent implementation is smart governance, where Pakatto Village has digitized the implementation of village government and public services as well as accountability and transparency in the use of village funds. Meanwhile, the other pillars of smart villages have been implemented, but still need improvement, coordination and technical guidance from the Gowa Regency Government and other related agencies. Supporting factors for the implementation of the smart village program that can be identified are the suitability between the program and the target group, the suitability between the program and the implementing organization and the suitability between the implementing organization and the target group. Meanwhile, inhibiting factors include available time and resources, a time lag in program results, the independence of the implementing organization and a lack of coordination and communication. Even though it is still one year away, there have already been impacts felt by the community, including better access to services, community empowerment in solving problems in the village and improving the quality of use of village funds.